Liver-related mortality in the United States: hepatitis C declines, non-alcoholic fatty liver and alcohol rise - Lee, Brian P.; Terrault, Norah A. (Translational Gastroenterology and Hepatology; Vol 4 (March 2019): Translational Gastroenterology and Hepatology, 2019)
With the advent of highly effective and accessible direct-acting antiviral (DAA) therapy for patients with hepatitis C virus (HCV), the landscape of chronic liver disease is rapidly changing. In the study by Kim et al. (1) using data from the U.S. Census and National Center for Health Statistics, a striking reduction in HCV-related mortality rates was observed from 8.14 per 100,000 persons in 2013 to 7.15 per 100,000 persons in 2016, coinciding with the approval of second generation DAAs. While inferential, as DAA use was not directly measured, these data align with other recent studies showing the association of DAAs with reversal of hepatic decompensation, reduced likelihood of liver transplant (LT) listing, and improved survival among patients with HCV-related cirrhosis (2,3). Collectively, evidence of population-level benefits of HCV treatment on liver and non-liver outcomes continues to be amassed, providing strong support of HCV elimination efforts in the U.S. and globally.